2019
DOI: 10.2147/rru.s174996
|View full text |Cite
|
Sign up to set email alerts
|

<p>Long-term renal function following zero ischemia partial nephrectomy</p>

Abstract: Partial nephrectomy (PN), also known as nephron sparing surgery, is considered as the first-line treatment in small renal masses, especially in T1/2 tumors, and is applied as a standard treatment in advanced centers. The main expected outcomes from an ideal PN are surgical margin negativity, minimal impairment in renal function, and any surgical complications. Many authors have defined PN techniques as “zero ischemia partial nephrectomy”, where surgery is performed without clamping the main renal artery in ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…Clinically, assessment of kidney function to urea measurement is less significant since blood urea can rise in clinical conditions devoid of kidney diseases such as bleeding in the upper gastrointestinal tract (Boga and Sönmez, 2019), high protein diet, dehydration and catabolism; or decline in liver disease (severe; Nwose et al , 2019), poor protein diet and starvation (Okoro and Farate, 2019). A normal functioning kidney filters the blood with urea nitrogen, but in kidney failure, the level of urea in the blood builds up (Rusul and Haider, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, assessment of kidney function to urea measurement is less significant since blood urea can rise in clinical conditions devoid of kidney diseases such as bleeding in the upper gastrointestinal tract (Boga and Sönmez, 2019), high protein diet, dehydration and catabolism; or decline in liver disease (severe; Nwose et al , 2019), poor protein diet and starvation (Okoro and Farate, 2019). A normal functioning kidney filters the blood with urea nitrogen, but in kidney failure, the level of urea in the blood builds up (Rusul and Haider, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on robotic-assisted or laparoscopic partial nephrectomy have reported that techniques such as off-clamping, selective-clamping, or on-clamping do not affect functional outcomes [17][18][19] . On the contrary, some studies provide supporting evidence on the hypothesis that ischemia techniques such as cold ischemia, off-clamping, or www.nature.com/scientificreports/ selective vascular clamping are beneficial to preserve postoperative renal function 1,6,[20][21][22][23][24] . Riccardo Bertolo et al endeavored to compare the functional outcomes between off-clamped and on-clamped robot-assisted partial nephrectomy, and showed that the off-clamp is more favorable to preserve postoperative eGFR than clamping the renal hilum 9 .…”
Section: Discussionmentioning
confidence: 99%
“…However, Riccardo Bertolo et al found that off-clamp showed a tendency towards better renal function recovery after partial nephrectomy than cold ischemia and warm ischemia technique 9 . Boga et al also reviewed that impairment of renal function in selective renal artery clamping technique and off-clamping technique was less significant than on-clamping 22 . Our study rather argues that zero/selective ischemia technique can be regarded as superior to cold ischemia technique.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with hilar clamping, it is associated with an improved postoperative renal function, without increasing the risk of complications rate [29]. However, this technique requires distal dissection of the artery branches, which can increase the risk of bleeding especially in patients with perirenal tissue adhesions and/or short segmental arteries [30,31].…”
Section: Ischemia Techniques In Nephron-sparing Surgerymentioning
confidence: 99%